Immune Evasive Effects of SARS-CoV-2 Variants to COVID-19 Emergency Used Vaccines - Zhang, Yandi; Banga Ndzouboukou, Jo-Lewis; Gan, Mengze; Lin, Xiaosong; Fan, Xionglin (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19) pandemic is the serious threat to global public health and social and economic development. A variety of vaccine platforms have been developed rapidly and unprecedentedly and at least 17 vaccines receive emergency use authorization. However, the causative pathogen severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has continued to evolve and mutate, emerging a large number of viral variants. Several variants have successfully become the predominant strains and spread out across the world, because of their ability to immune escape the pre-existing immunity after the prior infection or immunization. Here, we summarized prevalence and biological structure of the variants, as well as the efficacy of current used vaccines response to the SARS-CoV-2 variants, in order to provide a guidance on how to more rationally design vaccines against the variants.